Detection of Fiscal Illusion in the Regional Financial System of Special Autonomy Fund Recipients (Case Study in Aceh, Papua, and West Papua) - Bayu Aji Laksono; Mohammad Wahed (Publikasi Inspirasi Indonesia, 2026)
This study aims to detect the phenomenon of fiscal illusion within the regional financial system in areas receiving Special Autonomy Funds (Dana Otonomi Khusus) in Indonesia, particularly in the provinces of Aceh, Papua, and West Papua. The study is motivated by the high dependency of regional governments on central government transfers—especially Special Autonomy Funds—amid efforts to enhance regional fiscal independence. A quantitative descriptive approach is employed, analyzing data on Regional Own-Source Revenue, General Allocation Funds, Revenue Sharing Funds, and Special Autonomy Funds in relation to Regional Expenditures from 2009 to 2024. The findings reveal that Regional Own-Source Revenue and Special Autonomy Funds do not have a significant effect on Regional Expenditures, whereas General Allocation Funds and Revenue Sharing Funds have a significant influence. Most regional spending continues to rely on central government transfers, particularly Special Autonomy Funds, while Regional Own-Source Revenue contributions remain relatively low. This condition indicates the potential occurrence of fiscal illusion, characterized by a mismatch between public perception and the actual contribution of local revenues to regional development.